Mass Violence Againts Robbers in Jakarta Capatical City - Sardini, Nur Hidayat (International Journal of Psychosocial Rehabilitation, 2020)
—.This study departs from the basic understanding that a person or group of people who are perceived as perpetrators of crime can be rewarded with subsequent violence. The perpetrators felt that what he had done was an attempt to take revenge on (victims) who also always used violent methods in achieving their aims and objectives. The perpetrators considered that the way of mass violence was carried out far more effectively than the settlement through legal channels, because besides being considered too long but also unable to meet the psychological effects of revenge on the victims. In another sense, mass judgment is an effective settlement mechanism rather than a settlement mechanism through legal channels. The object of this research is mass violance, mass violence against motorbike robbers in the capital city of Jakarta.The results of the study conclude (1) the character of social habitus around Jakarta supports criminality. The economic, social, political and cultural climate of Jakarta and its surroundings is full of intense competition. To win the competition, residents around Jakarta must have skills according to employer qualifications. (2) The phenomenon of human movement around Jakarta, which takes place every day, continuously for years, and involves hundreds of thousands or even millions of people, from where they live in the surrounding area (hinterland) to centers of growth activity (growth centers), and proven to give birth to many psychologically vulnerable humans. (3) The occurrence of mass violance against robbers, is also caused by the learning process of local residents of similar events, both the experience of the community who have been victims of motorbike robbers, and similar events that have occurred in the country, especially around Jakarta.